Mutational Spectrum of Thalassemias and other Hemoglobinopathies in West Bengal, Eastern India. (December 2014) - Chatterjee, Tridip; Chakravarty, Amit; Chakravarty, Sudipa
Abstract Thalassemia, an autosomal recessive blood disease, shows a variety of clinical expression in terms of asymptomatic to severe blood transfusion dependence. More than 500 alleles have been characterized in or around the β-globin region. Most of the geographical regions have their own characteristic alleles that predominantly circulate within the communities present in that particular region. In this article, we try to throw some light to explore the spectrum of β-thalassemia (β-thal) alleles present in West Bengal, the eastern part of India. This study comprises thalassemia carriers and diseased persons from different districts of West Bengal. We not only explored the complete mutational spectrum of this state but we also tried to fix the critical range of the values of different hematological parameters [Hb A2, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH)] for the heterozygotes or carriers of β-thal with the same mutational background. At the same time, we also tried to evaluate the maximum weighted frequency of these parameters for the heterozygotes or carriers of β-thal with the same mutational background, so that by observing these cut-off values of standard hematological parameters, we were able to predict the carrier or diseased status for mass scale screening and also try to correlate the values of these parameters with different combinations of β-thal mutation-specific alleles that can be more informative in mass scale (carrier) screening.